Maturity Traits Related to Climate Adaptation Affect Quality Characteristics in Hard Red Spring Wheat. Issue 5 (9th August 2018) - Blake, N. K.; Varella, A. C.; Bicego, B.; Martin, J. M.; Cook, J. P.; Heo, H. -Y.; Acharya, R.; Sherman, J. D.; Nash, D.; Talbert, L. E.
Abstract : Maturity traits such as days to heading and days to physiological maturity have a large impact on agronomic characteristics of wheat ( Triticum aestivum L.) cultivars grown in specific environments. Extended green leaf and green glume duration after heading in hard red spring wheat have been shown to result in longer grain‐fill duration, increased kernel weight, and higher grain yield in dry environments. The genetic relationship between maturity traits, seed quality, and functional bread‐making characteristics was investigated for three sets of recombinant inbred lines derived from crosses between hard red spring wheat parents. Early heading date was correlated with increased seed quality as indicated by test weight and kernel weight in all three genetic populations. Days to heading was not consistently correlated with functional quality related to bread‐baking. Longer green glume and green leaf duration after heading were typically positively related to seed quality traits including test weight and kernel weight in the three populations. However, increased green leaf and green glume duration after heading were often negatively correlated with functional quality parameters related to bread baking. Our results suggest that selection for long green leaf or green glume duration after heading to stabilize grain yield in a warmer climate may also result in a decrease in bread‐making potential.